38 Developmental Screening Using the Infant Toddler Checklist at 18 Months and School Readiness at 4 to 6 Years. (21st October 2022) - Nurse, Kimberly; Janus, Magdalena; Birken, Catherine; Keown-Stoneman, Charles; Omand, Jessica; Maguire, Jonathon; Reid-Westoby, Caroline; Duku, Eric; Lebovic, Gerald; Mamdani, Muhammad; Simpson, Janis Randall; Tremblay, Mark; et al.
Abstract: Background: The American Academy of Pediatrics recommends developmental screening at multiple visits using both a general developmental tool and an autism spectrum disorder (ASD)-specific tool. The Canadian Paediatric Society recommends screening at a single visit at 18 months. There is no consensus on which tool is best suited for one-time screening. The Infant Toddler Checklist (ITC) identifies children who are at risk for communication impairment, may detect ASD, and may be a useful screening tool at the 18-month visit. Objectives: To examine the screening test accuracy of the ITC at the 18-month visit to predict school readiness at kindergarten age. Design/Methods: This prospective cohort study included children who attended primary care health supervision visits in Toronto, Canada. Parents completed the ITC at the 18-month visit and teachers completed the Early Development Instrument (EDI - a population-level measure of school readiness in kindergarten) at 4-6 years. An ITC screen is positive if there is concern for expressive speech delay (speech composite below the 10 th percentile) and/or other communication delay (social composite, symbolic composite or the total score below the 10 th percentile). Children were considered overall vulnerable on the EDI if at least one of five domains was below the 10 th percentile of the Ontario population: language and cognitive development; physical health and well-being; social competence; emotional maturity; communication skills and general knowledge. We calculated screening test properties with 95% confidence intervals (CIs), using EDI vulnerability as the criterion measure. We used multivariable regression models to examine the association between the ITC and EDI domains. Results: Of 293 children, 30 (10%) had a positive ITC. At follow-up, 54 (18%) children had a teacher-reported EDI vulnerability. The specificity (range, 87%-96%) and negative predictive value (range, 83%-95%) for the ITC were high; false positive rate was low (range, 4%-13%); sensitivity was low (range, 11%-37%). A positive ITC was associated with a lower score in EDI language and cognitive development (b= -0.62, 95% CI: -1.25, -0.18; P=0.046) and EDI communication skills and general knowledge (b= -1.08, 95% CI: -2.10, -0.17; P=0.036). We found no evidence of an association between ITC and EDI vulnerability. Conclusion: The ITC at 18 months had high specificity (87%-96%) suggesting that most children with a negative ITC will demonstrate school readiness at 4-6 years. False positive rates were low, minimizing over-diagnosis. The ITC, with its focus on speech and language, communication disorders and ASD, may be a candidate for screening at the 18-month visit.